Etuaptmumk - two-eyed seeing: Bringing together land-based learning and online technology to teach Indigenous youth about food - Renee Bujold; Ann Fox; Kerry Propser; Kara Pictou; Debbie Martin (Canadian Food Studies / La Revue canadienne des études sur l'alimentation, 2022)
In 2019 we began an intergenerational Land-based learning program with the goal of engaging a group of Mi’kmaw youth from a rural community in Nova Scotia with their Traditional Foodways. When COVID-19 and the physical distancing restrictions hit Nova Scotia, however, this changed how we implemented the project. We decided to bring youth together virtually and encourage self-directed Land-based learning. This paper describes the dilemmas we faced as we considered what initially seemed like a paradoxical relationship- using online technology to promote Land-based learning. Our aim is to not only draw attention to what we believe to be the centrality of the Land in understanding Indigenous foodways, but also the potential for online technology to enhance youth engagement on and with the Land. We begin by exploring Land-based learning and how it supports teaching about Traditional foodways and Indigenous culture, as well as the challenges and opportunities related to implementing Land-based pedagogy in a virtual environment. Using Etuaptmumk-Two Eyed Seeing as our lens, we argue that online technologies can support Land-based learning, providing principles of local culture are respected and the technology is compatible with community values.